Analysis of The Performance of Educational Institutions, With A Balanced Scorecard Approach - Takene, Konradus (Jurnal Indonesia Sosial Sains, 2024)
This study aims to measure the performance of SMA Seminari St. Rafael Kupang with a Balanced Scorecard approach. This research is a quantitative research with a descriptive design. The research was conducted by measuring the performance level of SMA Seminari St. Rafael Kupang through four aspects (perspectives) in the Balanced Scorecard, namely: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. The research instrument is in the form of questionnaires distributed to seminarians, which are primary data. There is also secondary data in the form of questionnaires (for educators and education personnel), school financial data, and other supporting documents and data. The core respondents in this study were seminarians. Additional respondents were educators and education personnel. The final results showed that the performance of the educational institution, SMA Seminari St. Rafael Kupang, was overall in the good category. Customer perspective performance is in the outstanding category, judging from the perceptions, satisfaction, and expectations of seminarians. Performance Financial perspective is in the good category, in terms of financial management requirements, namely economical, efficient, and effective. The performance of internal business processes is in a good category, judging from the operating processes that occur in this institution. The performance of learning and growth perspectives is a good category.